Photocatalytic pure water splitting with high efficiency and value by Pt/porous brookite TiO2 nanoflutes. (January 2020) - Cao, Shuang; Chan, Ting-Shan; Lu, Ying-Rui; Shi, Xinghua; Fu, Bing; Wu, Zhijiao; Li, Hongmei; Liu, Kang; Alzuabi, Sarah; Cheng, Ping; Liu, Min; Li, Tao; et al.
Abstract: We report the remarkable production of H2 and H2 O2 from pure water using porous brookite TiO2 nanoflutes decorated with Pt nanoparticles through two-electron photocatalytic intermediate water splitting (PIWS). The H2 production rate from deionized water (pH 7.0) was 9.8 ± 0.6 μmol mg −1 h −1, more than 12-fold and 230-fold higher than the reported TiO2 -based photocatalytic overall water splitting (POWS) and H2 /H2 O2 production systems, respectively. The apparent quantum yields (AQY) value can achieve 43.4%, which is the highest value compared with the reported TiO2 -based POWS systems and the commercial value for PIWS is 9-fold higher than that for POWS even ignoring the separation cost. The mechanism of the distinct performance was confirmed by DFT and experimental measurements. The present work provides a feasible strategy to significantly improve the process efficiency and value of photocatalytic water splitting in both pure water and seawater using natural sunlight. Graphical abstract: Image 1 Highlights: Remarkable photocatalytic production of H2 and H2 O2 from pure water (PIWS). The new porous brookite TiO2 nanoflutes show superior PIWS efficiency. The PIWS pathway proceeds by a kinetically favorable two-electron reaction. The commercial value for PIWS is 9-fold higher than H2 /O2 production systems.